2001
DOI: 10.4102/jsava.v72i2.627
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microorganisms associated with udder infections in dairy goats on small-scale farms in Kenya : short communication

Abstract: aThis study was carried out to determine the prevalence of intra-mammary bacterial infections in healthy dairy goats in the central Kenyan highlands, where the highest density of dairy goats in Kenya occurs, in order to formulate mastitis control measures in the flocks.The investigation was carried out in 7 dairy goat farmer groups. All the does that were in different stages of lactation from all the dairy goat groups were sampled once a month for 3 months. The number of does sampled were 130 in the 1st month,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 7 publications
(6 reference statements)
4
14
1
Order By: Relevance
“…Isolation of Acinetobacter sp. in large numbers from sample Y146R is interesting given that Ndegwa et al (2001) isolated Acinetobacter sp. from mastitic caprine glands.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of Acinetobacter sp. in large numbers from sample Y146R is interesting given that Ndegwa et al (2001) isolated Acinetobacter sp. from mastitic caprine glands.…”
Section: Discussionmentioning
confidence: 99%
“…18,27,28 Mycoplasma Mastitis Mycoplasma mastitis frequently is suspected when signs of clinical mastitis appear but repeated bacterial cultures are negative. 18,27,28 Mycoplasma Mastitis Mycoplasma mastitis frequently is suspected when signs of clinical mastitis appear but repeated bacterial cultures are negative.…”
Section: Other Species Associated With Clinical Mastitismentioning
confidence: 99%
“…Although the type of bacteria isolated from goats depends on geographical region, members of the Enterobacteriaceae, S. aureus, S. epidermidis, Staphylococcus lentus, and S. caprae are most commonly reported (Ndegwa et al 2001;Moroni et al 2005;Persson and Olofsson 2011;Chu et al 2012). Many of the bacteria isolated in this study corresponded to those previously reported.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, our primary interest was to determine whether these bacteriocins in crude samples are able to control pathogenic microorganisms associated with mastitis in dairy goats as these animals are of economical importance, not only in the state of Guanajuato, Mexico, but also in other regions in the world, including Taiwan, Sweden, Italy, Kenya, and Algeria (Ndegwa et al 2001;Moroni et al 2005;Barboza-Corona et al 2007;Chu et al 2012;Bourabah et al 2013). To our knowledge, no previous reports have been published on the use of bacteriocins of B. thuringiensis to control pathogenic bacteria associated with mastitis in dairy goats.…”
Section: Discussionmentioning
confidence: 99%